Analisis pengaruh pengetahuan awal, efikasi diri, kecerdasan emosional, perilaku belajar, dan budaya terhadap tingkat pemahaman akuntansi mahasiswa perbankan syariah - Indriyani, Fany (Journal of Accounting and Digital Finance, 2021)
The study aimed to examine the effect of prior knowledge, self-efficacy, emotional intelligence, learning behavior, and culture on the level of significance accounting understanding of Islamic banking students in Salatiga. This study uses primary data by providing questions in the form of questionnaires distributed to respondents who are students of the Islamic Banking Study Program, Faculty of Economics and Islamic Business, IAIN Salatiga. The sample was selected using the purposive sampling method. A total number of 180 questionnaires were sent out and 160 questionnaires can be processed. The data is processed by multiple linear regression analysis to prove the hypothesis. The results showed that partially the effect of prior knowledge has a significant effect on accounting understanding, although the four other variables, namely self-efficacy, emotional intelligence, learning behavior, and culture have no effect on the level of accounting understanding of Islamic banking students in other cities.